Efeito de compostos naturais no envelhecimento e em modelos de doença de Alzheimer no nematódeo Caernorhabditis elegans - Zamberlan, Daniele Coradini (2018)
During ageing, the cell repair system, including adaptative response to oxidative stress and unfolded protein degradation. In last decades, the increasing life expectancy, added to genetic and ambiental factors, has increasing neurodegenerative diseases incidence, as Alzheimer’s Disease (AD). Amyloid plaques in brain formed by amyloid-β (Aβ) protein aggregation mainly characterize AD. Antioxidant compounds from natural sources have demonstrated beneficial effects, mainly related to aging. In this way, this study aims to evaluate in vivo effects of chronic treatment with the ethanolic extract of Rosmarinus officinalis (eeRo) on aging and Paullinia cupana (GEE) on AD models in the Caernorhabditis elegans nematode, as well as to elucidate its mechanisms. For this, the wild-type strain and transgenic strains with βA expression were used as DA models. Behavioral assays, resistance to different types of stress, longevity, quantification of reactive oxygen species (ROS) and levels of the βA protein and silencing of genes involved in the stress response were performed. The data demonstrated that eeRo treatment decreases ROS levels and increases longevity and stress resistance, in a daf-16, hsf-1 and skn-1 dependent way. Regarding GEE, data demonstrated that the treatment reduced βA levels, delaying its toxic effects through the activation of HSF-1. Thus, in this study, we demonstrated compounds capable of reinforcing the cellular repair systems, offering new alternatives against aging and, related to GEE, prevention against the protein aggregation observed in AD.